The cyclicality of effective wages within employer-employee matches: evidence from German panel data - Silke Anger (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Using individual based micro-data from the German Socio-Economic Panel Study (SOEP), I analyze the cyclicality of real wages for male workers within employer-employee matches over the period 1984-2004, and compare different wage measures: the standard hourly wage rate, hourly wage earnings including overtime and bonus payments, and the effective wage, which takes into account not only paid overtime, but also unpaid working hours. None of the hourly wage measures is shown to exhibit cyclicality except for the group of salaried workers with unpaid overtime. Their effective wages react strongly to changes in unemployment in a procyclical way. Despite acyclical wage rates, salaried workers without unpaid hours but with income from extra payments, such as bonuses, experienced procyclical earnings movements. Monthly earnings were also procyclical for hourly paid workers who received overtime payments. The procyclicality of earnings revealed for Germany is of comparable size with the one in the U.S.
Keywords: E32; J31; 330; Wage cyclicality; effective wages; unpaid overtime; bonus payments; firm stayers; Reallohn; Konjunktur; Deutschland